Evaluation of the release profile, stability and antioxidant activity of a proanthocyanidin-rich cinnamon (Cinnamomum zeylanicum) extract co-encapsulated with α-tocopherol by spray chilling. (May 2017) - Tulini, Fabrício L.; Souza, Volnei B.; Thomazini, Marcelo; Silva, Marluci P.; Massarioli, Adna P.; Alencar, Severino M.; Pallone, Eliria M.J.A.; Genovese, Maria I.; Favaro-Trindade, Carmen S.
Abstract: Cinnamon has many health improving compounds such as proanthocyanidins, which also have potential for the prevention of damages caused by diabetes. Similarly, α-tocopherol is a natural antioxidant with important role on protection of fatty acids in membranes and lipoproteins. However, the addition of antioxidants in food may result in interaction with food matrix, low stability and unpleasant taste. In the present study, a proanthocyanidin-rich cinnamon extract (PRCE) ( Cinnamomum zeylanicum ) was co-encapsulated with α-tocopherol into solid lipid microparticles (SLMs) by spray chilling. The microparticles were characterized with regard to the physical and chemical properties, morphology, proanthocyanidin stability and release profile. SLMs were spherical with an average diameter of ca. 80 μm. Proanthocyanidins were highly stable in SLMs stored for up to 90 days at 5, 25 and 37 °C. Moreover, SLMs gradually released proanthocyanidins in simulated gastrointestinal fluids by a diffusional process, following a Korsmeyer-Peppas kinetic. Analyses of the antioxidant compounds indicated that PRCE components exhibited a higher scavenging capacity against reactive oxygen species (ROS) and reactive nitrogen species (RNS). Thus, the SLMs produced in the present study have potential for application in the development of new functional foods and nutraceuticals, also providing an alternative for the controlled release of proanthocyanidins and α-tocopherol into the intestine. Graphical abstract: Highlights: A proanthocyanidin-rich cinnamon extract (PRCE) was co-encapsulated with α-tocopherol Proanthocyanidins were highly stable in solid lipid microparticles (SLM) stored for up to 90 days SLM gradually released proanthocyanidins in simulated gastrointestinal fluids The release profile followed a Korsmeyer-Peppas kinetic (diffusional process) PRCE exhibited a higher scavenging capacity against reactive oxygen species and reactive nitrogen species.